The Relationship of Social Influence on Online Collaborative Learning in an E-Learning Environment - Abdul Wahid, Nur Ilyana; A.Gani, Norhaninah (Jurnal Evolusi, 2020)
This study investigates the impact of social influence on online collaborative learning within an e- learning environment, aiming to understand how social factors shape student engagement and learning outcomes. Employing a descriptive analytics approach, data was collected through a questionnaire to assess respondents' attitudes towards e-learning acceptance and social influence. The findings revealed a moderate acceptance of e-learning, influenced by usability, simplicity of use, and the quality of the e-learning system. Social influence emerged as a key determinant, emphasizing the significance of peer interactions, collaborative learning, and teacher involvement in enhancing learning outcomes and engagement. While the study acknowledges limitations such as potential response bias from self-reported data, future research could explore more objective measures of social influence and additional factors impacting student acceptance and engagement. This research contributes to the field by highlighting the crucial role of social influence in shaping attitudes and behaviors in online learning environments, offering valuable insights for educational technology and paving the way for further exploration of social dynamics in e-learning settings.